Exploring the Teaching of Language Variation Use from Early Children's Acquisition at School - Ridwin Purba; Resmi Resmi; Nanda Saputra; Herman Herman (Jurnal Obsesi : Jurnal Pendidikan Anak Usia Dini, 2022)
The purpose of this study was to look at language variations in early childhood speech at school. The method used in this research was descriptive qualitative. The subjects of this study were early childhood children at one of the Kindergarten school located in the city of Pematangsiantar. Language acquisition is obtained through the language of parents, as well as language in school and in the environment. The variety of languages obtained can be varied, the subjects studied used children as research subjects with different family backgrounds, there was a mixture of Batak Karo and Simalungun tribes, Batak Toba and Batak Karo, Batak Toba with Nias, Javanese with Batak. In early childhood, it is very easy to absorb language and it is easy to imitate the language obtained from parents, the environment and school so that the language used by children can vary. Data collection was carried out using the conversational and observational method of observing. The results obtained are that these five variations appear with various background factors. Dialect variations began to be used along with the development of his age at an early age, so that the acquisition of the language has begun to show its uniqueness.